Protective effect of aqueous fenugreek seed extract on sodium benzoate-induced hepatotoxicity and nephrotoxicity in albino rats (Journal of Hama University, 2022)
This study aimed to determine the effect of aqueous fenugreek seed extract on the levels of (AST, ALT, Urea, creatinine) in the serum of albino rats induced hepatotoxicity and nephrotoxicity with sodium benzoate,highlighting its protective efficacy.The study included 30 male adult albino mice of the Balb/c strain distributed into three experimental groups (10 mice in each group). The first group was a physiological control that was injected with 0.9% NaCl until the end of the experiment. The second group was the pathological control where it was injected with sodium benzoate in a dose 100 mg/kg of body weight daily for a month in order to create toxicity. While the third group. It is the preventive group, where it was injected within the peritoneum with benzoate at a dose of 100 mg/kg of body weight  and then aqueous extract of fenugreek seeds at a dose of 200 mg/kg of body weight simultaneously for a whole month. At the end of the experiment blood samples were collected from animals Experiment for biochemical analysis.The results of the statistical analysis showed the effectiveness of aqueous fenugreek seed extract in the prevention of hepatotoxicity and nephrotoxicity induced by benzoate, as it caused a significant (p
Keywords: fenugreek seed extract,hepatotoxicity ,nephrotoxicity, sodium benzoate. The white mice.